Fusion rate and complications of oblique lumbar interbody fusion and transforaminal lumbar interbody fusion in the treatment of lumbar degenerative diseases: a meta-analysis - Xiao, Xun; Duan, Heng; Pan, Xin; Zhao, Hua (Frontiers in Surgery, 2024)
Background There currently exists some controversy about the efficacy of oblique lumbar interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) in the treatment of lumbar degenerative diseases. Aim This study compares the application effects of OLIF and TLIF in lumbar degenerative diseases by reviewing the literature and using meta-analysis. Methods We included randomized controlled trials and cohort studies comparing TLIF and OLIF in the treatment of lumbar degenerative diseases. We searched for words such as “intervertebral disc degeneration,” “spinal fusion,” and “lumbar vertebrae” in the PubMed, Embase, and Cochrane Library databases. The search date was set from the establishment date of the database to October 2023. Two authors independently conducted document screening, data abstraction, and qualitative assessment. A meta-analysis was performed and adapted to RevMan5.3 software. The odds ratio (OR), weighted mean difference (WMD), and 95% CI were calculated by adopting a fixed-effect model (FEM) or a random-effect model (REM). Results A total of 18 cohort studies were included with 1,550 patients, of whom 806 patients underwent TLIF (TLIF group) and 744 patients underwent OLIF (OLIF group). There were no significant differences found in the fusion rate [OR = 1.58 (0.95, 2.64), P = 0.08], complication rate [OR = 1.25 (0.93, 1.68), P = 0.14], and visual analog scale for back pain (VAS-BP) [WMD = 0.00 (−0.13, 0.14), P = 0.96] between the two groups. Compared with the TLIF group, the OLIF group had a lower Oswestry disability index (ODI) [WMD = −0.62 (−1.03, −0.20), P = 0.003], a higher foramen height (FH) [WMD = 2.03 (1.42, 2.46), P < 0.001], a higher disc height (DH) [WMD = 1.69 (1.17, 2.22), P < 0.001], and a shorter length of stay (LOS) [WMD = −1.80 (−2.55, −1.05), P < 0.001]. Conclusion In the treatment of lumbar degenerative diseases, compared with TLIF, OLIF has more advantages in terms of improving the lumbar function, restoring the FH and DH, and shortening the LOS. Both methods have comparable fusion rates, complication rates, and lumbar pain improvements. Due to the small amount of research and unclear assessment of the risk of bias, high-quality, large-sample randomized controlled studies are required to prove it.